A Recent Supermassive Black Hole Binary in the Galactic Center Unveiled by the Hypervelocity Stars - Chunyang Cao; F. K. Liu; Shuo Li; Xian Chen; Ke Wang (The Astrophysical Journal Letters)
When a binary of early-type stars from the young stellar populations in the Galactic center (GC) region is scattered to the vicinity of the supermassive black hole (SMBH) Sgr A*, one of the components would be tidally ejected as an early-type hypervelocity star (HVS) and the counterpart would be captured on a tight orbit around Sgr A*. Dozens of B-type HVSs moving faster than the Galactic escape speed have been discovered in the Galactic halo and are produced most likely by the SMBH Sgr A*. However, the velocity distribution and in particular the deficit of the HVSs above 700 km s ^−1 is seriously inconsistent with the expectations of the present models. Here we show that the high-velocity deficit is due to the deficiency in close interactions of stars with the SMBH Sgr A*, because an orbiting intermediate-mass black hole (IMBH) of about 15,000 Solar mass kicked away slowly approaching stars 50–250 million years ago. The SMBH–IMBH binary formed probably after the merger of the Milky Way with the Gaia-Sausage-Enceladus dwarf galaxy, and coalesced about 10 million years ago, leading to a gravitational recoil of Sgr A* at a velocity of 0.3–0.5 km s ^−1 and to a change of the HVS ejection scenarios. The SMBH–IMBH binary scenario predicts the formation of the S-star cluster at the GC with the distribution of the orbital size and stellar ages that are well consistent with the observations.